Application of polyaniline carbon material as catalyst in removal of phenolic pollutants in wastewater by oxidative polymerization
Patent Information
- Application Number
- CN202611125643.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]现有技术中用于氧化聚合去除污水中酚类污染物的催化剂主要为金属氧化物催化剂,也有基于炭黑、碳纳米管、石墨烯、活性炭、生物质炭的碳基催化剂,上述催化剂均存在催化活性低、氧化剂用量高、酚类污染物聚合去除效率低的问题
[0011]有益效果:与现有技术相比,本发明具有如下显著的优点:本发明利用聚苯胺碳化材料作为催化剂氧化聚合去除污水中酚类污染物,聚苯胺碳化材料对过硫酸盐具有高的催化效率,能够快速活化过硫酸盐诱导苯酚发生氧化聚合去除,从而实现在低氧化剂用量下具有高的反应速度和污染物去除率。
Smart Images

Figure CN122877902A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the application of polyaniline carbonization material as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater. Background Technology
[0002] Advanced oxidation technologies are one of the important means to remove recalcitrant organic pollutants. Among them, oxidation systems represented by persulfate or perdisulfate have attracted widespread attention due to their strong oxidizing capacity and wide applicable pH range. However, traditional advanced oxidation systems mainly rely on the deep mineralization of pollutants, which often suffers from problems such as high oxidant consumption, limited electron utilization efficiency, high treatment costs, and potential side reactions during the reaction process.
[0003] Recent studies on the oxidative polymerization removal pathway of organic pollutants have shown that some electron-rich aromatic pollutants can preferentially undergo oxidative polymerization under suitable catalysts and oxidation systems, and are removed from the aqueous phase through the deposition, adhesion, or transfer of polymerization products on the catalyst surface. Compared with pathways relying solely on mineralization degradation, the oxidative polymerization removal approach has certain advantages in reducing oxidant consumption, shortening reaction time, and improving treatment selectivity.
[0004] In the existing technology, the catalysts used for oxidative polymerization to remove phenolic pollutants from wastewater are mainly metal oxide catalysts, and there are also carbon-based catalysts based on carbon black, carbon nanotubes, graphene, activated carbon, and biochar. All of the above catalysts have the problems of low catalytic activity, high oxidant dosage, and low polymerization removal efficiency of phenolic pollutants. Summary of the Invention
[0005] Purpose of the invention: The purpose of this invention is to provide an application of polyaniline carbonized material as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater. Polyaniline carbonized material can significantly improve the catalytic efficiency for persulfate, achieving high reaction rate and removal rate with low oxidant dosage.
[0006] Technical Solution: The application of the polyaniline carbonized material described in this invention as a catalyst for the oxidative polymerization removal of phenolic pollutants from wastewater is as follows: the polyaniline carbonized material is mixed with water containing phenol to obtain a mixed solution; persulfate is added to the mixed solution to carry out a catalytic reaction, so as to induce the oxidative polymerization of phenolic pollutants and remove them from the aqueous phase; wherein, the molar ratio of persulfate to phenol is 0.5~4:1, and the dosage of polyaniline carbonized material is 0.2~0.3 g / L.
[0007] The mixed solution is sonicated for 15-20 minutes, then stirred at 400-500 rpm for 15-20 minutes to ensure uniform dispersion of the catalyst in the system. The persulfate is sodium persulfate. The reaction time is no more than 60 minutes; after the reaction, the solution is filtered through a 0.22 μm PES aqueous filter membrane.
[0008] The polyaniline carbonized material was prepared by the following method, with the specific steps as follows: (1) The aniline monomer and the initiator were dissolved in acetic acid solution, and after sonication, aniline precursor solution and initiator precursor solution were obtained; the initiator precursor solution was added to the aniline precursor solution under low temperature conditions for oxidative polymerization to obtain polyaniline precursor; (2) The obtained polyaniline precursor was carbonized at high temperature under a nitrogen atmosphere, and then soaked in ethanol and deionized water in sequence to obtain polyaniline carbonized material.
[0009] In step (1), the initiator is ammonium persulfate, and the molar ratio of aniline monomer to initiator is 1:1~2, preferably 1:1; the ultrasonic frequency is 20~40kHz, and the ultrasonic time is 20~30min, preferably 37kHz, and the time is 30min. The aniline precursor solution and the oxidant precursor solution are pre-cooled at 1~4℃ for 5~15min; the oxidative polymerization time is 12~30h.
[0010] In step (2), the carbonization temperature is 850~950℃, preferably 900℃; the carbonization time is 2~3h, preferably 2h; and the heating rate is 2~2.5℃ / min, preferably 2℃ / min. The polyaniline carbonization material needs to be soaked in ethanol for 1~2h and in deionized water for 0.5~1h, preferably in ethanol for 1h and in deionized water for 0.5h. Soaking can effectively remove the carbonization byproducts remaining on the surface of the product and enhance its catalytic effect.
[0011] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: The present invention uses polyaniline carbonized material as a catalyst to oxidatively polymerize and remove phenolic pollutants in wastewater. Polyaniline carbonized material has high catalytic efficiency for persulfate and can quickly activate persulfate to induce oxidative polymerization and removal of phenol, thereby achieving high reaction rate and pollutant removal rate with low oxidant dosage. Attached Figure Description
[0012] Figure 1 This is a scanning electron microscope image of the polyaniline carbonized material prepared in Example 1; Figure 2 The nitrogen adsorption-desorption curve of the polyaniline carbonized material prepared in Example 1 is shown. Figure 3This is a comparison chart of the effect of different oxidant dosages on the removal rate of phenol polymerization in water in Examples 2-4; Figure 4 Example 5 shows the polymerization removal rate of phenol in water. Figure 5 Example 6 shows the polymerization removal rate of sulfamethoxazole in water. Figure 6 The removal rates of phenol in water by different catalysts (metal oxides, multi-walled carbon nanotubes, and polythiophene carbonized materials) in Comparative Examples 1-3 were measured. Detailed Implementation
[0013] Example 1 The method for preparing the polyaniline carbonized material of the present invention includes the following steps: (1) 0.262 g of aniline monomer and 8.778 g of ammonium persulfate were added to 100 mL of acetic acid solution with a concentration of 0.4 mol / L, wherein the molar ratio of aniline monomer to ammonium persulfate was 1:1; aniline precursor solution and ammonium persulfate precursor solution were obtained, and the aniline precursor solution and ammonium persulfate precursor solution were subjected to sonication, wherein the sonication frequency was 37 kHz and the sonication time was 30 min; (2) The ultrasonic aniline precursor solution and ammonium persulfate precursor solution were pre-cooled at 1~4℃ for 10 min, and then the ammonium persulfate precursor solution was added to the aniline precursor solution. Oxidative polymerization was carried out at 25℃ for 24 h to obtain dark green polyaniline precursor. (3) The polyaniline precursor (PANI precursor) was placed in a tube furnace, and nitrogen gas was first purged at 400 mL / min for 10 min. Then, the temperature was increased to 900 °C at a rate of 2 °C / min under a nitrogen atmosphere and held for 2 h. After natural cooling, the material was removed and soaked in ethanol for 1 h, followed by soaking in deionized water for 0.5 h to obtain polyaniline carbonized material (C-PANI). Characterization results of C-PANI obtained in Example 1 showed that C-PANI has a microstructure similar to carbon nanotubes (e.g., Figure 1 As shown in the figure, the specific surface area can reach 37.6 m². 2 / g (e.g.) Figure 2 As shown in the figure, its high specific surface area gives it a large number of reactive sites in subsequent applications as a catalyst.
[0014] Example 2 The polyaniline carbonized material prepared in Example 1 was used as a catalyst for oxidative polymerization to remove phenolic pollutants from wastewater. The specific application process is as follows: (1) The polyaniline carbonization material is thoroughly mixed with an aqueous solution containing phenol to obtain a mixed solution; the initial concentration of phenol in the mixed solution is 15 mg / L, and the amount of catalyst (polyaniline carbonization material) added is 0.2 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system. (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.08 mmol / L (molar ratio of sodium persulfate to phenol is 0.5:1). Start timing immediately after reaction and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane, and analyze the phenol concentration in the filtered liquid. The analytical results are as follows: Figure 3 As shown, the oxidative polymerization removal rate = COD removal rate in solution / target pollutant removal rate. In Example 2, after 60 min of reaction, the phenol removal rate reached 51%, and the oxidative polymerization removal rate was 97%.
[0015] Example 3 The polyaniline carbonized material prepared in Example 1 was used as a catalyst for oxidative polymerization to remove phenolic pollutants from wastewater. The specific application process is as follows: (1) The polyaniline carbonization material is thoroughly mixed with an aqueous solution containing phenol to obtain a mixed solution; the initial concentration of phenol in the mixed solution is 15 mg / L, and the amount of catalyst (polyaniline carbonization material) added is 0.2 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system. (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.32 mmol / L (molar ratio of sodium persulfate to phenol is 2:1). Start timing immediately after reaction and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane, and analyze the phenol concentration in the filtered liquid. The analytical results are as follows: Figure 3 As shown, in Example 3, after 60 minutes of reaction, the removal rate of phenol reached 96%, and the removal rate of oxidative polymerization was 98%.
[0016] Example 4 The polyaniline carbonized material prepared in Example 1 was used as a catalyst for oxidative polymerization to remove phenolic pollutants from wastewater. The specific application process is as follows: (1) The polyaniline carbonization material is thoroughly mixed with an aqueous solution containing phenol to obtain a mixed solution; the initial concentration of phenol in the mixed solution is 15 mg / L, and the amount of catalyst (polyaniline carbonization material) added is 0.2 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system. (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.64 mmol / L (molar ratio of sodium persulfate to phenol is 4:1). Start timing immediately after reaction and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane, and analyze the phenol concentration in the filtered liquid. The analytical results are as follows: Figure 3 As shown, in Example 4, after 60 minutes of reaction, the phenol removal rate reached 99%, and the oxidative polymerization removal rate was 58%.
[0017] Example 5 The polyaniline carbonized material prepared in Example 1 was used as a catalyst for oxidative polymerization to remove phenolic pollutants from wastewater. The specific application process is as follows: (1) The polyaniline carbonization material is thoroughly mixed with an aqueous solution containing phenol to obtain a mixed solution; the initial concentration of phenol in the mixed solution is 15 mg / L, and the amount of catalyst (polyaniline carbonization material) added is 0.3 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system. (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.32 mmol / L. Start timing immediately and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane. Analyze the phenol concentration in the filtered liquid. The analytical results are as follows: Figure 4 As shown, in Example 5, after 60 minutes of reaction, the removal rate of phenol reached 99%, and the removal rate of oxidative polymerization was 94%.
[0018] Example 6 The polyaniline carbonized material prepared in Example 1 was used as a catalyst for oxidative polymerization to remove sulfamethoxazole pollutants from wastewater. The specific application process is as follows: The specific application process is as follows: (1) The polyaniline carbonization material is thoroughly mixed with an aqueous solution containing sulfamethoxazole to obtain a mixed solution; the initial concentration of sulfamethoxazole in the mixed solution is 15 mg / L, and the dosage of catalyst (polyaniline carbonization material) is 0.2 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system; (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.12 mmol / L (molar ratio of sodium persulfate to sulfamethoxazole is 2:1). Start timing immediately and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane. Analyze the concentration of sulfamethoxazole in the filtered liquid. The analytical results are as follows: Figure 5 As shown, in Example 6, after 60 minutes of reaction, the removal rate of sulfamethoxazole reached 54%, and the removal rate of oxidative polymerization was 97%.
[0019] Comparative Example 1 Compared to Example 3, Comparative Example 1 uses cerium dioxide, a metal oxide, as a catalyst for oxidative polymerization to remove phenolic pollutants from wastewater. The specific application process is as follows: (1) The polyaniline carbonization material is thoroughly mixed with an aqueous solution containing phenol to obtain a mixed solution; the initial concentration of phenol in the mixed solution is 15 mg / L, and the amount of catalyst (cerium dioxide) added is 0.2 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system. (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.32 mmol / L (molar ratio of sodium persulfate to phenol is 2:1). Start timing immediately after reaction and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane, and analyze the phenol concentration in the filtered liquid. The analytical results are as follows: Figure 6 As shown, the phenol removal rate was 3% after 60 min of reaction.
[0020] Comparative Example 2 Compared to Example 3, Comparative Example 2 uses multi-walled carbon nanotubes as a catalyst for oxidative polymerization to remove phenolic pollutants from wastewater. The specific application process is as follows: (1) The polyaniline carbonized material is thoroughly mixed with an aqueous solution containing phenol to obtain a mixed solution; the initial concentration of phenol in the mixed solution is 15 mg / L, and the amount of catalyst (multi-walled carbon nanotubes) added is 0.2 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system. (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.32 mmol / L (molar ratio of sodium persulfate to phenol is 2:1). Start timing immediately after reaction and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane, and analyze the phenol concentration in the filtered liquid. The analytical results are as follows: Figure 6 As shown, the phenol removal rate was 60% after 60 min of reaction.
[0021] Comparative Example 3 Compared to Example 3, Comparative Example 3 uses polythiophene carbonization material as a catalyst for oxidative polymerization to remove phenolic pollutants from wastewater. The specific application process is as follows: (1) The polyaniline carbonization material is thoroughly mixed with the phenol-containing aqueous solution to obtain a mixed solution; the initial concentration of phenol in the mixed solution is 15 mg / L, and the amount of catalyst (polythiophene carbonization material) added is 0.2 g / L; the mixed solution is first sonicated for 15 min, and then stirred at 400 rpm for 15 min to ensure that the catalyst is uniformly dispersed in the system. (2) Add sodium persulfate to the mixed solution from step (1) at a concentration of 0.32 mmol / L (molar ratio of sodium persulfate to phenol is 2:1). Start timing immediately after reaction and take samples at 0, 5, 10, 15, 20, 30, and 60 min. Filter each sample through a 0.22 μm PES aqueous filter membrane, and analyze the phenol concentration in the filtered liquid. The analytical results are as follows: Figure 6 As shown, the phenol removal rate was 56% after 60 min of reaction.
Claims
1. An application of a polyaniline carbonization material as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that, The specific application process is as follows: polyaniline carbonized material is mixed with water containing phenol to obtain a mixed solution; persulfate is added to the mixed solution to carry out a catalytic reaction, so as to induce oxidative polymerization of phenolic pollutants and remove them from the aqueous phase; wherein, the molar ratio of persulfate to phenol is 0.5~4:1, and the dosage of polyaniline carbonized material is 0.2~0.3g / L.
2. The application of the polyaniline carbonization material according to claim 1 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: After sonicating the mixed solution for 15-20 minutes, stir it at 400-500 rpm for 15-20 minutes, and then add persulfate to carry out the catalytic reaction.
3. The application of the polyaniline carbonization material according to claim 2 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: The reaction time is no more than 60 minutes.
4. The application of the polyaniline carbonization material according to claim 2 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: The persulfate is sodium persulfate.
5. The application of the polyaniline carbonization material according to claim 1 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: The polyaniline carbonized material was prepared by the following method, with the specific steps as follows: (1) The aniline monomer and the initiator were dissolved in acetic acid solution, and after sonication, aniline precursor solution and initiator precursor solution were obtained; the initiator precursor solution was added to the aniline precursor solution under low temperature conditions for oxidative polymerization to obtain polyaniline precursor; (2) The obtained polyaniline precursor was carbonized at high temperature under a nitrogen atmosphere, and then soaked in ethanol and deionized water in sequence to obtain polyaniline carbonized material.
6. The application of the polyaniline carbonization material according to claim 5 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: In step (1), the initiator is ammonium persulfate, and the molar ratio of the aniline monomer to the initiator is 1:1~2.
7. The application of the polyaniline carbonization material according to claim 5 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: In step (1), the frequency of the ultrasound is 20~40kHz and the duration of the ultrasound is 20~30min.
8. The application of the polyaniline carbonization material according to claim 5 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: In step (1), the aniline precursor solution and the oxidant precursor solution are pre-cooled at 1~4℃ for 5~15min; the oxidative polymerization time is 12~30h.
9. The application of the polyaniline carbonization material according to claim 5 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: In step (2), the carbonization temperature is 850~950℃, the carbonization time is 2~3h, and the heating rate is 2~2.5℃ / min.
10. The application of the polyaniline carbonization material according to claim 5 as a catalyst in the oxidative polymerization removal of phenolic pollutants from wastewater, characterized in that: In step (2), soak in ethanol for 1-2 hours and in deionized water for 0.5-1 hour.